Sevoflurane Inhibition of the Slowly Activating Delayed Rectifier K+ Current in Guinea Pig Ventricular Cells - Shigehiro Shibata; Kyoichi Ono; Toshihiko Iijima (Elsevier, 2004)
Single ventricular cells were enzymatically isolated from guinea pig hearts and the effects of sevoflurane on the delayed rectifier K+ current were investigated by the patch clamp method. The rapidly (IKr) and slowly activating delayed rectifier K+ current (IKs) were isolated using chromanol 293B, a selective blocker for IKs or E4031 (N-[4-[[1-[2-(6-methyl-2-pyridinyl) ethyl]-4-piperidinyl]carbonyl]phenyl]methanesulfonamide dihydrochloride), a blocker for IKr. Sevoflurane and halothane decreased IKs in a concentration-dependent manner with an IC50 value of 0.38 mM for sevoflurane and 1.05 mM for halothane. IKs inhibition was characterized by suppression of maximum conductance with little effect on activation kinetics. Inhibition occurred immediately after anesthetic application and recovered upon wash-out. In contrast to the marked inhibition of IKs, IKr was hardly affected by sevoflurane. Under the current clamp, sevoflurane prolonged the action potential duration in a reversible manner and this effect was more marked when IKr was inhibited by E4031. The results suggest that sevoflurane inhibits IKs, and not IKr, in a concentration-dependent manner at clinically relevant concentrations. The resulting prolongation of ventricular repolarization may partly account for the clinical observation of excessive QT prolongation by these anesthetics. Keywords:: QT prolongation, delayed rectifier K+ current, sevoflurane, chromanol 293B, E4031